TRIANGULATION IN (POST) DIVORCE FAMILY DYNAMICS: A SYSTEMIC FAMILY APPROACH - Sretić, Sanja (Politeia, 2026)
The research has been conducted with the aim of determining parents’ perception of triangulation as a pattern of family functioning in relevance to characteristics of family dynamics: the way the divorce procedure ended, the quality of parents` communication, as well as their decision making about children in the (post) divorce period. The data is collected via DFOR PRP scale constructed on the basis of two standardized instruments and the parents` questionnaire constructed specially for the needs of this research, to question sociodemographic and control variable. The results show statisctically significant difference in the level of percepted triangulation in relation to the characteristics of family dynamics. Triangulation is more present with parents whose divorce process was full of conflicts and has included the network of different institutions, with no or only conflict communicatiоn, and the ones with no agreement on any parental decisions, that is to say, where children themselves make crucial decisions, based on the perception of the parents included in the research. The obtained results point to the necessity of early recognition of disfunctional family dynamics as a risk factor for forming coalition between a parent and a child/children based on their age and timely intervention through educational and psychotherapeutical work with the parents.